The Influence of the Problem Based Model on the Ability to Write Explanatory Text of Class VIII Students at SMPN 24 Jambi City - Fitra Alauddina; Eddy Pahar Harahap; Lusia Oktri Wini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this study was to see the influence of the PBL model on student success to write explanatory texts in student which was carried out in August-September of the 2022/2023 academic year. The method used in this reasearch is a two group pretest posttest design. In the experimental group learning, the leraning model was the Problem Based Learning, while in the control group learning, the conventional method was used. Each learning group was initially given a test in the form of a pretest and at the end of the learning was given a test in the form of a posttest. This study uses population and sample in the study. The population is all eighth grade students.The total sample was 64 people. The instrument used was a learning test to write explanatory text. Based on calculations, the average value obtained from the results of the explanation text in the experimental class posttest was 74,6. This value of the control class, namely 46,4. Data analysis requirements were tested using a normality test. Sample data can be said to be a normal distribution if Asymp. Sig. (2-tailed) > 0.05. Based on the results of the homogeneity test on samples from both classes, it shows that the sample distribution is normal. This is indicated by obtaining 0.0315 > 0.05 in the experimental class and control class with a significance value in both Based On Mean classes >0.05. Next, hypothesis testing was carried out using the Wilcoxon test. The hypothesis testing criteria is rejection based on the analysis prerequisite test. The sig. value obtained is 0.000. So therefore, formulated that there is an influence of the Problem Based Learning model on the learning to write explanatory texts for class VIII students at SMPN 24 Kota Jambi City is accepted. The PBL model can be used to achieve learning goals. Using the Problem Based Learning model also maes learning more varied and not boring.